SUVERVISI GURU MENGGUNAKAN ALAT PENILAIAN KOMPETENSI GURU (APKG) PADA PENILAIAN KOMPONEN KEPRIBADIAN DAN SOSIAL GURU DI SDN JURUMUDI 5 KOTA TANGERANG - Dahlia Dahlia; Bambang Afriadi (Jurnal Evaluasi Pendidikan, 2020)
This study uses an evaluation analysis model with qualitative and quantitative method approaches. Evaluation research is not intended to test hypotheses but is intended to improve the program or policy undertaken. This research was conducted at SDN Jurumudi 5 Kota Tangerang. The time of the study is odd semester 2018/2019 by evaluating the personality of the teacher at SDN Jurumudi 5 Kota Tangerang. The most important finding of this study is that the positive attitude of the teacher has positively influenced the personality of students and also the reputation of the teacher's performance. More than that, a teacher who has a good personality will create a good school atmosphere too. From the results of the research carried out, work ethic is an important concern.